Estimation of Stature from Percutaneous Length of Radius and Ulna in Nepalese Medical Students - Kandel, Jwala; Yadav , Salmalee (Journal of Nobel Medical College, 2025)
Background: Stature estimation is an integral part of forensic identification along with race, sex and age. The relevance is greater when decomposed, mutilated and burnt bodies are brought for autopsy. Previous studies have shown isolated body parts and bones reasonably accurate in estimating stature. Present study aims at estimating stature from percutaneous lengths of radius and ulna in Nepalese medical students.Material and Methods: A cross sectional study was conducted from April 2024 to September 2025 in Nobel Medical College Teaching Hospital, Nepal; including 412 Nepalese medical students (182 males and 230 females). After taking informed consent; Stature was measured with standard stadiometer, while Percutaneous Radial Length (PCRL) and Percutaneous Ulnar Length (PCUL) were measured by flexible measuring tape using standard techniques. Data was analyzed using Statistical Package for Social Sciences (SPSS Ver. 20) software. Pearson’s correlation coefficient was used to find correlation of stature with PCRL and PCUL, and its significance tested by t-test (p < 0.005). Linear regression equations were derived to estimate stature from PCRL and PCUL.Results: Stature showed significant positive linear correlation with PCRL and PCUL in both sexes. The derived linear regression equation for stature estimation for males was 116.478 + 2.108*PCRL and 107.056 + 2.326*PCUL, for females was 104.006 + 2.356*PCRL and 107.228 + 2.087*PCUL and for entire cases was 88.145 + 3.132*PCRL and 86.793 + 2.994*PCUL.Conclusion: Stature shows significant positive correlation with PCRL and PCUL in Nepalese medical students. Hence stature estimation can be done from PCRL and PCUL in Nepalese context.